Transforming the Landscape of Women’s Entrepreneurship and its Impacts in Kanchanpur District - Bist, Kusum (Journal of Jayaprithvi Multiple Campus, 2025)
The role of entrepreneurship is multifaceted and crucial for the economic development of the nation as well as for women’s. The study site is Kanchanpur, selected purposefully. This study attempted to explore the impact of women’s entrepreneurship in Kanchanpur. For the study, the survey method under quantitative design was used and 200 informants from different small-scale industries, business units, micro-finance companies, and cooperatives (based on taking loans) in Kanchanpur. The purpose of this study is to seek how their activity can contribute to economic empowerment and poverty alleviation and improve the social economic condition of women and uplift of women’s status and empower them. By focusing on analyzing the contributions of women entrepreneurs and evaluating their economic activities, the research seeks to provide a comprehensive understanding of the role of women’s entrepreneurship. Additionally, by evaluating the effectiveness of women’s entrepreneurship in improving living standards, the study aims to highlight the appreciable benefits experienced by women in terms of their quality of life. The findings of this paper reveal the fact that the act of entrepreneurship empowered women to improve their decision-making power and economic independence, stimulating employment opportunities at the local level. There is gender inequality in this sector. The study concludes that women’s lifestyles are changing despite facing many problems. The result of this study indicates that women’s entrepreneurship is essential for social economic development and empowerment of women as well as for gender equality. This study establishes how women entrepreneurs are successful in changing their lifestyles, and it also helps them to become financially independent and uplift their economic conditions.